Pulmonary Hypertension in Heart Failure. Epidemiology, Right Ventricular Function, and Survival - Gerges, Mario; Gerges, Christian; Pistritto, Anna-Maria; Lang, Marie B.; Trip, Pia; Jakowitsch, Johannes; Binder, Thomas; Lang, Irene M. (American journal of respiratory and critical care medicine, 2015)
Patients with pulmonary hypertension due to left heart disease (PH-LHD) and a diastolic pulmonary vascular pressure gradient ≥ 7 mm Hg, representing PH out of proportion to pulmonary arterial wedge pressure, have pulmonary vascular disease and increased mortality. Little information exists on this condition, recently labeled as "combined pre- and post-capillary PH" (Cpc-PH). To investigate epidemiology, risk factors, right ventricular function, and outcomes in patients with chronic heart failure and Cpc-PH. The study population was identified from a retrospective chart review of a clinical database of 3,107 stable patients who underwent first diagnostic right heart catheterization and from a prospective cohort of 800 consecutive patients at a national university-affiliated tertiary center. The retrospective cohort had 664 patients with systolic heart failure (SHF) and 399 patients with diastolic heart failure (DHF), 12% of whom were classified as Cpc-PH. The prospective cohort had 172 patients with SHF (14% Cpc-PH) and 219 patients with DHF (12% Cpc-PH). Chronic obstructive pulmonary disease (P = 0.034) and the tricuspid annular plane systolic excursion to systolic pulmonary artery pressure ratio (P = 0.015) predicted Cpc-PH in SHF. Younger age (P = 0.004), valvular heart disease (P = 0.046), and the tricuspid annular plane systolic excursion to systolic pulmonary artery pressure ratio predicted Cpc-PH in DHF (P = 0.016). Right ventricular-pulmonary vascular coupling was worse in Cpc-PH patients (end-systolic elastance to effective arterial elastance [Ees/Ea]: SHF: 1.05 ± 0.25; P = 0.002; DHF: 1.17 ± 0.27; P = 0.027) than in those with isolated post-capillary PH (Ees/Ea: SHF: 1.52 ± 0.51; DHF: 1.45 ± 0.29). Cpc-PH is rare in chronic heart failure. Right ventricular-pulmonary vascular coupling is poor in Cpc-PH and could be one explanation for dismal outcomes.